Diminished Dynamic Physical Performance Is Associated With Orthostatic Hypotension in Geriatric Outpatients. Issue 3 (July 2019) - de Bruïne, Eline S.; Reijnierse, Esmee M.; Trappenburg, Marijke C.; Pasma, Jantsje H.; de Vries, Oscar J.; Meskers, Carel G. M.; Maier, Andrea B.
Abstract : Background and Purpose: Orthostatic hypotension (OH), a blood pressure drop after postural change, is a highly prevalent and disabling syndrome in older adults. Yet, the association between physical performance and OH is not clearly established. The aim of this study was to determine whether different types of physical performance are associated with OH in a clinically relevant population of geriatric outpatients. Methods: This cross-sectional study included 280 geriatric outpatients (mean age: 82.2 years, standard deviation: 7.1). Orthostatic hypotension was determined using intermittently measured blood pressure and continuously measured blood pressure in a random subgroup of 58 patients. Physical performance was classified into a dynamic type (4-m Walk Test, Chair Stand Test, and Timed Up and Go test) and a static type (standing balance tests, handgrip strength). Associations were analyzed using logistic regression models with adjustments for age, sex, weight, and height. Results: Diminished physical performance on the Chair Stand Test was associated with OH measured intermittently. Diminished physical performance on all dynamic physical domains (4-m Walk Test, Chair Stand Test, and Timed Up and Go test) was associated with OH measured continuously. Static physical performance was not significantly associated with OH. Conclusion: Dynamic physical performance tests with a substantial postural change and center of mass displacement were significantly associated with OH. The influence of physical performance on OH in daily routine activities should be further explored to establish counteracting interventions.